Design and Development of SmartKuliner: A Multimedia-Enhanced Web Platform for Culinary Product Promotion - Muhammad, Nibras Faiq; Pramono; Andhini, Asmara (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This paper presents the design and development of SmartKuliner, a web-based culinary marketplace enhanced with multimedia features to support culinary product promotion. The platform integrates visual design, user-centered interface, and multimedia content to improve user engagement and trust. The development process adopts a multimedia development life cycle (MDLC) and emphasizes usability testing. Results indicate that SmartKuliner provides an effective medium for culinary businesses to promote products and for users to discover trusted local culinary items.